Integration of Islamic principles in education of physiology of human digestive system - Radiah, Abdul Ghani; Habibah, Hassan; Athirah Nur, Ahmad Rosli; Ahmed Shogar, Ibrahim Adam; Ahmad Irfan, Ikmal Hisham (IIUM Press, 2018)
Introduction At the rise of the Islamic Empire, the Muslims were at the forefront in all sciences, technology, medicine and so forth and contributed significantly to the advancement of knowledge in Western Civilization. Unfortunately, the Muslims scientists were ignorant of Islamic knowledge and follow Western teachings and read the textbook written by non-Muslims which lack in the integration between Tawhid and science. To regain our glorious past, the embedding of tawhid, or the Islamisation of human knowledge should be the aim of Muslims today.